Mobile Internet Usage among Adolescents and Young Adults in Iran: A Sociological Survey - Ghasemi, Vahid; Rabiei, Khatoon; Davoodi, Sara; Rabiei, Habib (Journal of History Culture and Art Research, 2017)
This article aims to study the phenomenon of the tendency of adolescents and young adults to the mobile Internet as a social issue in the information era. The phenomenon of the Internet and the mobile Internet has risen in the developed counties as a consequence of increase in the development of electronic communication networks and it has many functions for individuals, family and society. This paper is derived from a survey research in 2013 on the status of this phenomenon in Iran. The statistical population of this research is the adolescents and young adults from 13 to 22 years old in Isfahan who have access to the mobile Internet. The sample population is 193 and the results indicate that there is an intense tendency to the mobile Internet in Iran. This seems normal in comparison with the developed countries. Also, according to the results of the study, 90.3% of adolescents and young people have mobile phones and mobile Internet and have access to the Internet mostly via the Irancell SIM cards and mobile Wi-Fi (they do not use Rightel due to the prohibition of senior clergies). Due to the easy access, the mobile Internet is their favorite. More than browsers, they use online games and social networks (especially Facebook). According to this study no social impairment (eg. Internet addiction, lack of accountability, educational impairment, social isolation, etc) because of the adolescents’ tendency to the mobile Internet was observed in them.